Screen Time for Preschool Children: Learning from Home during the COVID-19 Pandemic - Indri Hapsari Susilowati; Susiana Nugraha; Sudibyo Alimoeso; Bonardo Prayogo Hasiholan (SAGE Publishing, 2021)
Because of the COVID-19 pandemic, the Indonesian Government enacted a study at home policy for all students. This policy also applied to preschool children aged 2 to 6 years old. The purpose of the research was to examine the duration and impact of digital media use by preschool children in urban areas in Indonesia during weekdays and weekends. Data were collected using a validated questionnaire called the Surveillance of digital-Media hAbits in earLy chiLdhood Questionnaire (SMALLQ ® ). A total of 951 parents or guardians (17-70 years old) who had preschool children volunteered to complete the questionnaire online. Preschool children have been using screen media since infancy, and the time they spend on-screen time is more than 1 hour per day. The digital media most used were mobile phones (91.6%), followed by television (86.1%) and computers (61%). The parents realized the impact and the importance of limiting time of screen media, but it difficult to prevent their children from using it, especially when learning from home. Hence, there is a need different approach to learning from home, especially to manage the duration of screen time for preschool children.